Counseling-Based Education Management Strategy in Shaping the Sportsmanship Character of Physical Education Students - Darmawati, Darmawati; Mahmud, Syahruddin; Rizal, A. (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to explore and analyze the implementation of educational management strategies based on guidance and counseling in developing sportsmanship character among Physical Education students at Megarezky University. The study employed a qualitative case study design, as it allows for an in-depth understanding of the complex phenomena related to the internalization of sportsmanship values through guidance and counseling services. Data were collected through triangulation techniques, including in-depth interviews with students and academic supervisors, participant observation during counseling activities, and documentation in the form of modules, activity records, photographs, and videos. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, conclusion drawing, and data verification. The findings reveal that the systematic implementation of guidance and counseling-based educational management strategies had a positive impact on the development of students’ sportsmanship character. Students demonstrated greater awareness of the importance of fair play, respect for opponents, adherence to rules, improved cooperation, and better emotional management. Mentoring, group counseling, and self-reflection activities were found to be effective in fostering self-awareness, conflict management skills, and the practical application of ethical values in sports. The implications of this study confirm that guidance and counseling can serve as a holistic, adaptive, participatory, and sustainable model for character development. However, limitations related to the focus on a single study program, variations in individual responses, and the lack of long-term evaluation still need to be considered.